amaXhosa circumcision : stories of manhood and mental health - Vivian, Lauraine Margaret Helen (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book investigates amaXhosa circumcision and the psychological processes involved. Lauraine Vivian employs concepts such as resilience, orthodoxy, broken men, and reciprocity to examine the experiences of men who have developed mental health issues in relation to their initiation into manhood. The chapters cover sensitive topics such as physical injury, pain, harm, and women's agency. Drawing on the stories of over seventy amaXhosa men, the book provides rare insight into circumcision and psychotic experience"--
Negotiating patriarchy -- Resounding resilience in amaXhosa circumcision -- amaXhosa women in circumcision -- Embedding pain in memory -- Circumcision, manhood and psychosis -- amaXhosa metaphor in psychosis -- An unbroken man -- Negotiating harm -- Women's advocacy -- The depth of contestation.
OCLC-licensed vendor bibliographic record.
Keywords: Circumcision -- Social aspects -- South Africa; Circumcision -- Psychological aspects; Xhosa (African people) -- Rites and ceremonies; Xhosa (African people) -- Social life and customs; Xhosa (African people) -- Mental health; Xhosa (African people) -- Medicine; Masculinity -- South Africa; Sex role -- South Africa; Sex role -- Psychological aspects; SOCIAL SCIENCE / Anthropology / General